Use of complementary approaches in pregnant women with a history of miscarriage. (February 2018) - Huberty, Jennifer; Matthews, Jeni; Leiferman, Jenn A.; Lee, Chong
Highlights: Approximately 39% of pregnant women with a history of miscarriage use a complementary approach. Pregnant women with a history of miscarriage most frequently use prayer, yoga, and massage. Pregnant women with a history of miscarriage are more likely to use a complementary approach than those without. Abstract: Objectives: To describe the use of complementary approaches in pregnant women with a history of miscarriage and to investigate whether a miscarriage is associated with the use of complementary approaches during their pregnancy. Design: A cross-sectional survey was distributed to pregnant women residing in the United States (N = 890). Results: Women who had a history of miscarriage, were Caucasian, were college educated, reported a high income, had low depression scores, and had low anxiety scores (all P < 0.001) were more likely to use complementary approaches. In pregnant women with a history of miscarriage (N = 193), the most frequently reported complementary approaches used were prayer (22.3%), yoga (15%), massage (14.5%), chiropractic (13%), and meditation (11.4%). Finally, after adjustment for age, race, education, and income, the odds of using a complementary approach in women with a history of miscarriage was 1.8 (95% CI: 1.3, 2.5, P < 0.001) as compared with women without a history of miscarriage (model 1). Associations persisted after additional adjustment for depression, anxiety, and stress; the odds of using a complementary approach in women with a history of miscarriage was 1.7 (95% CI: 1.2, 2.4, P < 0.001) (model 2), compared with women without a history of miscarriage. Conclusions: Findings from this study may help inform future studies for pregnant women with a history of miscarriage and may also provide information about appropriate strategies in which health care providers can refer their patients.